Children's time use in the Longitudinal Study of Australian Children: Data quality and analytical issues in the 4-5 year cohort - Baxter, Jennifer (My University, 2005)
The first wave (2004) of the Longitudinal Study of Australian Children included time use diaries (TUD) for children aged around one year old and a second group aged around four to five years old. This paper demonstrates some of the ways these data can be used. A significant issue in the use of the data is that a large amount is missing. The paper analyses the missing data for children in the four to five year cohort, and highlights some of the strengths and weaknesses of the TUD data. It presents an overview of the diary and the resulting data; examines data quality issues, including missing data; presents an option for imputing missing activity data; and analyses the TUD data by time of day.
4
Technical paper
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology